Book Review Essay: The Relevance of Richard Rorty to Management Research - Nord, Walter R.; Freeman, R. Edward (Academy of Management Review, 2004)
The article reviews the book ?The Relevance of Richard Rorty to Management Research,? by R. Edward Freeman.